2014
DOI: 10.1016/j.bbamcr.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection elicited by P2Y13 receptors against genotoxic stress by inducing DUSP2 expression and MAPK signaling recovery

Abstract: Nucleotides activating P2Y13 receptors display neuroprotective actions against different apoptotic stimuli in cerebellar granule neurons. In the present study, P2Y13 neuroprotection was analyzed in conditions of genotoxic stress. Exposure to cisplatin and UV radiation induced caspase-3-dependent apoptotic cell death, and p38 MAPK signaling de-regulation. Pre-treatment with P2Y13 nucleotide agonist, 2methyl-thio-ADP (2MeSADP), restored granule neuron survival and prevented p38 long-lasting activation induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 51 publications
3
12
0
1
Order By: Relevance
“…As expected, dusp2 expression was abolished by the inhibition of both ERK signaling and PI3K activity, and by the P2Y 13 specific antagonist MRS2211. These data confirmed that dusp2 gene was under the regulation of PI3K/ERK1/2 mediated signaling stimulated by P2Y 13 receptors in granule neurons [43].…”
Section: P2y13 Receptor Mediated Signaling Through Erk1/2-mapk In Grasupporting
confidence: 75%
See 1 more Smart Citation
“…As expected, dusp2 expression was abolished by the inhibition of both ERK signaling and PI3K activity, and by the P2Y 13 specific antagonist MRS2211. These data confirmed that dusp2 gene was under the regulation of PI3K/ERK1/2 mediated signaling stimulated by P2Y 13 receptors in granule neurons [43].…”
Section: P2y13 Receptor Mediated Signaling Through Erk1/2-mapk In Grasupporting
confidence: 75%
“…As expected, P2Y 13 receptor-mediated dephosphorylating effect on p38 as well as its prosurvival actions during cisplatin treatment were prevented by both P2Y 13 specific antagonist MRS2211 and the inhibitor of tyrosine phosphatases orthovanadate. Therefore, P2Y 13 activity on DUSP2 expression also contributed to neuroprotection against genotoxic stress [43] (Fig. 5).…”
Section: P2y13 Receptor Mediated Signaling Through Erk1/2-mapk In Gramentioning
confidence: 97%
“…We have now extended these data, showing no significant changes for the remaining receptors in a TLE patient cohort, with the only exception being P2Y 13 displaying lower levels. Of interest, P2Y 13 activation has been shown to exert neuroprotective effects in vitro; therefore, the reduction in P2Y 13 levels could contribute to increased vulnerability to seizure‐induced neurodegeneration. We did observe some differences between our mouse model of epilepsy and the TLE patient brain.…”
Section: Discussionmentioning
confidence: 99%
“…P2Y 1 receptor antagonists improve recovery from traumatic brain injury (Choo et al, 2013). A recent paper reports that neuroprotection against genotoxic stress is elicited by P2Y 13 receptor activation (Morente et al, 2014). The P2Y-like receptor, GPR17, is a sensor of brain damage and reacts to the release of nucleotides and cysteinyl leukotrienes in a focal ischaemia model (Lecca et al, 2008).…”
Section: Neuroprotection Against Trauma Ischaemia and Strokementioning
confidence: 99%